TINJAUAN KAPASITAS, HAMBATAN SAMPING DAN KINERJA JALAN PADA KAWASAN KOMERSIAL DAN KAWASAN PENDIDIKAN DI KOTA MATARAM - ROHANI ROHANI; I DEWA MADE ALIT KARYAWAN; JUNIATI HAPSAH (Universitas Mahasaraswati Mataram, 2021)
The traffic performance of the commercial and educational areas is influenced by the volume flow and road capacity. One of the impacts on traffic performance is side friction. The purpose of this study was to compare traffic flow, side friction, road capacity and performance in the commercial and educational areas by degree of saturation. Analyze and assess the relationship between side constraints on volume, capacity and degree of saturation. This study uses secondary data from previous studies. Jalan Dr. Wahidin and Jalan Panca Usaha as commercial area roads. Jalan Gajah Mada and Jalan Bung Karno as educational areas. The results of the analysis show that the roads in the commercial area have side barriers, high volume and degree of saturation and low capacity. The level of Service E. Meanwhile, education area roads have low volume, high capacity and low degree of saturation. The level of service C. From the regression analysis, the side friction has a very significant effect on the volume, capacity and degree of saturation. It can be seen from the value (r) in the range 0.7 <r <0.9 indicating a strong correlation and 0.9 <r <1 indicating a very strong correlation